2n+7-7n=33-11n+10

Simple and best practice solution for 2n+7-7n=33-11n+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n+7-7n=33-11n+10 equation:


Simplifying
2n + 7 + -7n = 33 + -11n + 10

Reorder the terms:
7 + 2n + -7n = 33 + -11n + 10

Combine like terms: 2n + -7n = -5n
7 + -5n = 33 + -11n + 10

Reorder the terms:
7 + -5n = 33 + 10 + -11n

Combine like terms: 33 + 10 = 43
7 + -5n = 43 + -11n

Solving
7 + -5n = 43 + -11n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '11n' to each side of the equation.
7 + -5n + 11n = 43 + -11n + 11n

Combine like terms: -5n + 11n = 6n
7 + 6n = 43 + -11n + 11n

Combine like terms: -11n + 11n = 0
7 + 6n = 43 + 0
7 + 6n = 43

Add '-7' to each side of the equation.
7 + -7 + 6n = 43 + -7

Combine like terms: 7 + -7 = 0
0 + 6n = 43 + -7
6n = 43 + -7

Combine like terms: 43 + -7 = 36
6n = 36

Divide each side by '6'.
n = 6

Simplifying
n = 6

See similar equations:

| 3+-1u=0 | | 2t-4t=8 | | 8g-15=73 | | 1+-4u=0 | | 8c-(-19)=59 | | s=6*7+64t-16t^2 | | 1.5(9x-3)=-4+8x | | h+30=180 | | 8c-(-19)=58 | | 5x+3=-x-2 | | -8+2g=-2 | | 5x+5=-10forx | | 2(w+5)=12 | | 4(x-a)+5b=5x+aforx | | ps+qr=r | | 15-5y=y+11+3y | | X+7=3x+11 | | 2x-(3+4x)=7 | | 10*K-5*k=1 | | 4z-6=5z | | P^3+125= | | 8xsquared+x= | | 2x^4+2x-17x=-3 | | 3(2x+7)=30 | | 4u^2-13u+3=0 | | 3x+2+4*3x-1=279 | | 2x^4+2x-17forx=-3 | | 5x(6-4)= | | 38.6-5.6x=4.2x-30 | | 2x^2+18+10=-6 | | 6.7x=5.2x+2.3 | | 12cd+15c= |

Equations solver categories